Pengaruh Biaya Produksi dan Harga Jual Terhadap Pendapatan Petani Cengkih di Kabupaten Sinjai, Indonesia - Muh. Asyraf Assidiqi; Akbar Akbar; Nurdin Nurdin (AGRIBIOS, 2026)
This study aims to analyze the effect of production costs and selling prices on the income of clove farmers. The research employed a quantitative approach using multiple linear regression analysis. Data were collected from 45 clove farmers selected through simple random sampling from a population of clove farmers in the study area. Primary data were obtained through structured interviews and questionnaires, while secondary data were collected from relevant institutions and previous studies. The results indicate that production costs have a positive and significant effect on farmers’ income, suggesting that higher production expenditures, when managed efficiently, are associated with increased income levels. Selling prices also show a positive and significant effect on farmers’ income, indicating that price improvements directly enhance farmers’ revenue. Simultaneously, production costs and selling prices significantly influence clove farmers’ income. These findings highlight the importance of efficient cost management and favorable selling prices in improving clove farmers’ income. The study provides empirical evidence that can support policymakers and stakeholders in formulating strategies to enhance income stability and economic welfare of clove farmers, particularly in clove-producing regions.